2003
DOI: 10.1162/089892903321107846
|View full text |Cite
|
Sign up to set email alerts
|

Common and Segregated Neuronal Networks for Different Languages Revealed Using Functional Magnetic Resonance Adaptation

Abstract: The effect of word repetition within and across languages was studied in English-Chinese bilinguals who read rapidly presented word pairs in a block design and an event-related fMRI study. Relatively less increase in MR signal was observed when the second word in a pair was identical in meaning to the first. This occurred in the English-only and mixed-languages conditions. Repetition-induced reductions in BOLD signal change were found in the left lateral prefrontal and lateral temporal regions in both types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
68
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 47 publications
14
68
1
1
Order By: Relevance
“…Alternatively, because subjects in the present study also learnt new sounds in addition to new visual forms, our results are also consistent with the notion that the fusiform is involved in phonological processing, or in integrating high-order visual form with phonology (Price and Devlin, 2003). In fact, many existing observations might be compatible with both the top-down modulation hypothesis and the lexical processing hypothesis, including the word frequency effect (Kronbichler et al, 2004), the cross-language and cross-script priming effect (Chee et al, 2003;Nakamura et al, 2005). Further studies on patients with focused lesion in this area would help to clarify this issue.…”
Section: Phonological and Semantic Training And Fusiform Activationsupporting
confidence: 89%
See 1 more Smart Citation
“…Alternatively, because subjects in the present study also learnt new sounds in addition to new visual forms, our results are also consistent with the notion that the fusiform is involved in phonological processing, or in integrating high-order visual form with phonology (Price and Devlin, 2003). In fact, many existing observations might be compatible with both the top-down modulation hypothesis and the lexical processing hypothesis, including the word frequency effect (Kronbichler et al, 2004), the cross-language and cross-script priming effect (Chee et al, 2003;Nakamura et al, 2005). Further studies on patients with focused lesion in this area would help to clarify this issue.…”
Section: Phonological and Semantic Training And Fusiform Activationsupporting
confidence: 89%
“…Because the two words share the same phonology and semantic identity, it is possible that the priming effect occurs at the phonological and/or semantic level, but not at the pre-lexical abstract visual word level. Consistent with this view, previous research also showed cross-language (Chee et al, 2003) and cross-script (Nakamura et al, 2005) priming effect in the fusiform region, but as well as in several other language areas. Thus, the exact mechanisms for how language experiences modulate the priming effect in fusiform cortex need to be elucidated.…”
Section: Introductionsupporting
confidence: 72%
“…Previous studies showed that these regions would be activated in bilingual production tasks and other bilingual processing tasks involving phonological and semantic retrieval (Bleser et al, 2003;Chee et al, 1999Chee et al, , 2001Chee et al, , 2003Klein et al, 1995Klein et al, , 1999Klein et al, , 2006Price et al, 1999;Tan et al, 2005).…”
Section: Imaging Resultsmentioning
confidence: 99%
“…One last line of research that started to make inroads into L1-L2 IS processes in the late twentieth century was the burgeoning field of neuroimaging psycholinguistic studies. The new technology, such as FUNCTIONAL MAGNETIC RESONANCE IMAGING (fMRI) or POSITRON EMISSION TOMOGRAPHY (PET), was able to offer, for the first time, vivid images of brain areas and patterns of activation involved in IS activity among L2 learners and bilinguals (e.g., Kim et al 1997;Price, Green & von Studnitz 1999;Chee, Soon & Lee 2003 Rather than dealing specifically with L2 IS, that is, fully internalized social speech, several researchers in the late twentieth century focused on the PS of L2 learners or bilinguals, both as the externalization of IS and as an early stage in the internalization of the L2. Two early studies explored the self-regulatory function of PS among adult L2 learners (Lantolf & Frawley 1984;Frawley & Lantolf 1985), whereas Diaz, Padilla & Weathersby (1991) focused on selfregulatory PS among bilingual preschoolers.…”
Section: Background For the Study Of L2 Is/psmentioning
confidence: 99%